Profil Penyimpanan Obat LASA (Look Alike Sound Alike) Pada Beberapa Apotek di Kota Medan - Dasopang, Eva Sartika; Utami, Adinda; Hasanah, Fenny; Siahaan, Desy Natalia; Harefa, Niken Septriani (Pengurus Pusat Ikatan Apoteker Indonesia, 2022)
Abstract: Drug production in the current era is quite rapid so that many drugs have similar names and pronunciation and almost the same packaging known as LASA (Look Alike Sound Alike). The number of LASA drugs on the market must be considered, especially their storage. Improper storage of LASA drugs can cause drug administration errors to patients Objective: to see how LASA drug storage and LASA drug items are in several pharmacies in Medan city. The research was conducted by direct observation at the sampled pharmacies using an observation form table through a check list system, then calculated the percentage of LASA storage standards based on pharmaceutical service standards in pharmacies. This study involved 14 pharmacies that were willing to be involved in this study from the many pharmacies in Medan city, data were taken from December 2021 to March 2022. This study shows that only 50% of the 14 pharmacies sampled have implemented LASA (Look Alike Sound Alike) drug storage, while the other 50% have not implemented the LASA (Look Alike Sound Alike) drug storage system in accordance with statutory regulations, namely Permenkes number 58 of 2014. The implementation of LASA drug storage according to Permenkes No. 58 of 2014 is still quite low in Medan city.